At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
1) [tex]\frac{(-2)^{-5}}{(-2)^{-10}}=-32[/tex]
2) [tex]2^{-1}.2^{-4} = \frac{1}{32}[/tex]
3) [tex](-\frac{1}{2} )^3.(-\frac{1}{2} )^2=-\frac{1}{32}[/tex]
4) [tex]\frac{2}{2^{-4}} = 32[/tex]
Step-by-step explanation:
1) [tex]\frac{(-2)^{-5}}{(-2)^{-10}}[/tex]
Solving using exponent rule: [tex]a^{-m}=\frac{1}{a^m}[/tex]
[tex]\frac{(-2)^{-5}}{(-2)^{-10}}\\=(-2)^{-5+10}\\=(-2)^{5}\\=-32[/tex]
So, [tex]\frac{(-2)^{-5}}{(-2)^{-10}}=-32[/tex]
2) [tex]2^{-1}.2^{-4}[/tex]
Using the exponent rule: [tex]a^m.a^n=a^{m+n}[/tex]
We have:
[tex]2^{-1}.2^{-4}\\=2^{-1-4}\\=2^{-5}[/tex]
We also know that: [tex]a^{-m}=\frac{1}{a^m}[/tex]
Using this rule:
[tex]2^{-5}\\=\frac{1}{2^5}\\=\frac{1}{32}[/tex]
So, [tex]2^{-1}.2^{-4} = \frac{1}{32}[/tex]
3) [tex](-\frac{1}{2} )^3.(-\frac{1}{2} )^2[/tex]
Solving:
[tex](-\frac{1}{2} )^3.(-\frac{1}{2} )^2\\=(-\frac{1}{8} ).(\frac{1}{4} )\\=-\frac{1}{32}[/tex]
So, [tex](-\frac{1}{2} )^3.(-\frac{1}{2} )^2=-\frac{1}{32}[/tex]
4) [tex]\frac{2}{2^{-4}}[/tex]
We know that: [tex]a^{-m}=\frac{1}{a^m}[/tex]
[tex]\frac{2}{2^{-4}}\\=2\times 2^4\\=2(16)\\=32[/tex]
So, [tex]\frac{2}{2^{-4}} = 32[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.